Sifat Organoleptik Dan Kandungan Gizi Japanese Cheesecake Substitusi Tepung Kacang Merah Garut Dan Penambahan Tepung Daun Kelor Sebagai Snack Alternatif Pencegah Stunting - Putri, Hera Tiara; Sumarto; Karimah, Ima (NUTRIASIK: Jurnal Terapan Gizi dan Pangan Fungsional Kesehatan, 2026)
Based on SSGI 2024, the prevalence of stunting in Indonesia is 19.8%, in Tasikmalaya City it reaches 27.1%. Protein, calcium, iron, and zinc deficiencies are the main causes of stunting. Prevention efforts can be done by consuming nutritious foods, one of which is Japanese cheesecake using local ingredients such as garut red bean flour and moringa leaf flour. This research aims to determine the organoleptic characteristics and nutritional content of Japanese cheesecake. The nutritional content of Japanese cheesecake F1 per 100 grams is 281 kcal of energy, 13 g of protein, 15 g of fat, 23 g of carbohydrates, 264 mg of calcium, 3 mg of iron, and 6 mg of zinc which can meet 50% of the protein needs of toddlers, 26% of calcium needs, 25% of iron needs and 128% of zinc needs.